Lifetime prevalence of syphilis infection among predominantly Black sexual and gender minorities living with HIV in Atlanta, Georgia: a cross-sectional analysis. Issue 2 (17th February 2023) - Wiginton, John Mark; Eaton, Lisa A.; Kalinowski, Jolaade; Watson, Ryan J.; Kalichman, Seth C.
ABSTRACT: Objectives: Syphilis infection disproportionately impacts Black sexual and gender minorities (SGM) in the United States. The extent of this impact among those living with HIV has been minimally examined. This study sought to examine lifetime syphilis prevalence and associated factors in a community sample of predominantly Black SGM living with HIV in the Southeastern US. Design: Participants (N = 174) enrolled in a stigma-mitigation trial for people living with HIV in Atlanta, Georgia, completed a sub-study involving testing for Treponema pallidum antibodies, indicative of lifetime syphilis infection. We performed chi-square and Fisher's exact tests to assess sociodemographic and healthcare differences by presence/absence of lifetime syphilis infection. Results: Most participants identified as non-Hispanic Black (n = 142/174; 81.6%) and cisgender male (n = 146/174; 83.9%). More than two thirds (n = 120/174) identified as gay/homosexual. We documented a 55.7% (n = 97/174) lifetime prevalence of syphilis infection and observed differences by sexual identity, with 77.3% (n = 75/97) of those screening positive reporting gay/homosexual identity relative to 58.4% (n = 45/77) of those screening negative (chi-square[1] = 7.8, p < 0.010). Conclusion: Findings underscore how syphilis prevention efforts have missed the most marginalized, warranting a renewed, comprehensive strategy for improving the sexual health of Black SGM. Embedding targeted, respectful community engagement, expanded testing access, and healthcare provider training into broader sexual health and psychosocial wellness efforts is needed.